Combined paleohistological and isotopic inferences of thermometabolism in extinct Neosuchia, using Goniopholis and Dyrosaurus (Pseudosuchia: Crocodylomorpha) as case studies. Issue 2 (May 2022) - Faure-Brac, Mathieu G.; Amiot, Romain; de Muizon, Christian; Cubo, Jorge; Lécuyer, Christophe
Abstract: The evolution of thermometabolism in pseudosuchians (Late Triassic to the present) remains a partly unsolved issue: extant taxa (crocodilians) are ectothermic, but the clade was inferred ancestrally endothermic. Here we inferred the thermometabolic regime of two neosuchian groups, Goniopholididae (Early Jurassic to Late Cretaceous) and Dyrosauridae (middle Cretaceous to late Eocene), close relatives of extant crocodilians, in order to elucidate the evolutionary pattern across Metasuchia (Early Jurassic to the present), a clade comprising Neosuchia (Early Jurassic to the present) and Notosuchia (Middle Jurassic until the late Miocene). We propose a new integrative approach combining geochemical analyses to infer body temperature from the stable oxygen isotope composition of tooth phosphate and paleohistology and phylogenetic comparative methods to infer resting metabolic rates and red blood cell dimensions. † Dyrosaurus and † Goniopholis share with extant crocodilians similar lifestyles, body forms, bone tissue organization, body temperatures, metabolic rates, and red blood cell dimensions. Consistently, we infer ectothermy for † Dyrosaurus and † Goniopholis with the parsimonious implication of neosuchians and metasuchians being primitively ectothermic.